2016
DOI: 10.1111/maps.12715
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and magneto‐structural study of the Maâdna structure (Talemzane, Algeria): Insights on its age and origin

Abstract: International audienceThe Maâdna structure is located approximately 400 km south of Algiers (33°19' N, 4°19' E) and emplaced in Upper-Cretaceous to Eocene limestones. Although accepted as an impact crater on the basis of alleged observations of shock-diagnostic features such as planar deformation features (PDFs) in quartz grains, previous works were limited and further studies are desirable to ascertain the structure formation process and its age. For this purpose, the crater was investigated using a multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…They have defined evidence for carbonate melting as effects resulting from shock metamorphism. In contrast, Lamali et al (2016, 2020) pointed out the previous authors’ misinterpretation of an unusual breccia or what appears as black varnish on weathered limestone and/or some type of outcrops (e.g., Pliocene breccias or neoformed concretions), as melting materials. An analogy was already made by Lamali et al (2016, 2020) between these litho‐type zones, within and outside of the crater, and referred to their fieldwork and petrographic analysis of their large number of samples.…”
Section: Geological Settingmentioning
confidence: 97%
See 2 more Smart Citations
“…They have defined evidence for carbonate melting as effects resulting from shock metamorphism. In contrast, Lamali et al (2016, 2020) pointed out the previous authors’ misinterpretation of an unusual breccia or what appears as black varnish on weathered limestone and/or some type of outcrops (e.g., Pliocene breccias or neoformed concretions), as melting materials. An analogy was already made by Lamali et al (2016, 2020) between these litho‐type zones, within and outside of the crater, and referred to their fieldwork and petrographic analysis of their large number of samples.…”
Section: Geological Settingmentioning
confidence: 97%
“…1a). Lamali et al (2016) used topographic profiles constructed from Shuttle Radar Topography Mission (SRTM) data to indicate an eccentricity of about 1.093. These authors identified a simple bowl shape for the structure with a slightly elliptical topographic depression, with long and short axes of 1.75 and 1.6 km in N‐S and E‐W edge dimensions, respectively.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…A piece of evidence comes from the publication survey (i.e., 2000-2015), revealing that only less than 1% of the worldwide output of scientific papers have been published in the (BENKHALDOUN et al 2005;GILLON et al 2017). Algeria is also focusing on meteorites and impact craters with the help of international collaborations (LAMALI et al 2016;SAHOUI et al 2016). Since 2015, the Arabian Geosciences Union have launched a special section on planetary science and astrobiology for PSS scientists across northern Africa and the Middle East.…”
Section: Collaborative Researchmentioning
confidence: 99%
“…Emphasis was given on the African impact structures and meteorites, considered with geological and/or geophysical approaches (e.g., Lamali et al. ; Sahoui et al. ).…”
Section: The Scientific Sessionsmentioning
confidence: 99%